Saandix0
Rozwiązane

2. Oblicz:
a) –15 + (-67) + 37
C) -7 + 4 + (-2) + 6
b) -12 + 13 + (-14) + 15
d) 12 + (-4) + (-9) + 9 + (-8)
prosze NIE o same wyniki​



Odpowiedź :

Lea3

a) -15 + (-67) + 37 = -15 - 67 + 37 = -82 + 37 = -45

b) -7 + 4 + (-2) + 6 = -3 - 2 + 6 = -5 + 6 = 1

c) -12 + 13 + (-14) + 15 = 1 - 14 + 15 = -13 + 15 = 2

d) 12 + (-4) + (-9) + 9 + (-8) = 12 - 4 - 9 + 9 - 8 = 12 - 4 - 8 = 8 - 8 = 0

Odpowiedź:

a) –15 + (-67) + 37 = -15 - 67 + 37 = -45

c) -7 + 4 + (-2) + 6 = -7 + 4 - 2 + 6 = 1

b) -12 + 13 + (-14) + 15 = -12 + 13 - 14 + 15 = 2

d) 12 + (-4) + (-9) + 9 + (-8)= 12 - 4 - 9 + 9 - 8 = 0

Mam nadzieje, że pomogłam :)

Szczegółowe wyjaśnienie: